STUDENTS' MATHEMATICAL THINKING SKILL VIEWED FROM CURIOSITY THROUGH PROBLEM-BASED LEARNING MODEL ON INTEGRAL CALCULUS - Zetriuslita Zetriuslita; Rezi Ariawan (Jurnal Infinity, 2021)
This study aims to find out the improvement of students’ mathematical critical thinking viewed from curiosity through teaching materials with Problem Based Learning model. This is quasi-experimental research. The samples are, where the overall population consists of 75 samples divided into two classes.  This research employed a simple random sampling technique.  The instruments were the mathematical critical thinking skill test and curiosity questionnaire. The technique of data collection was carried out with test and non-test techniques. The data were analyzed through a two-way Anova test. Based on the analysis and interpretation of the research findings, it was found that: there was an improvement in students’ mathematical critical thinking skill from High curiosity by using teaching materials with Problem Based Learning model; 1) There was an improvement from  Average curiosity through learning with Integral Calculus teaching materials; 2) There was an improvement from Low curiosity; 3) There was no improvement from the level of curiosity (High,  Medium,  Low) through Problem-based Learning. 4) There was no influence between the level of curiosity and learning in improving students’ mathematical critical thinking skills. Do more in-depth studies related to improving mathematical critical thinking skills by reviewing other affective aspects.